Advancing the Circular Economy: The Role of Policy, Innovation, and Sustainable Finance in Mitigating Textile Microplastic Pollution - Polavaram, Sindhuri (Tufts University Tisch Library, 2025)
Thesis (M.S.)--Tufts University, 2025.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Jeffrey Rosen, and Shafiqul Islam.; Keyword: Sustainability